2020
DOI: 10.3390/nu12020395
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition in Sepsis: A Bench-to-Bedside Review

Abstract: Nutrition therapy in sepsis is challenging and differs from the standard feeding approach in critically ill patients. The dysregulated host response caused by infection induces progressive physiologic alterations, which may limit metabolic capacity by impairing mitochondrial function. Hence, early artificial nutrition should be ramped-up and emphasis laid on the post-acute phase of critical illness. Caloric dosing is ideally guided by indirect calorimetry, and endogenous energy production should be considered.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 89 publications
(90 reference statements)
1
46
0
11
Order By: Relevance
“…Intravenous nutrition has been linked to an increased incidence of hyperglycemia (which is independently associated with increased mortality), increased risk of infection, and increased morbidity in septic patients [ 9 , 10 , 11 ]. Enteral nutrition also carries risk and has been associated with an increased incidence of diarrhea, nausea, vomiting, bowel ischemia, pulmonary aspiration, and hyperglycemia [ 12 , 13 ]. Full enteral nutrition, in particular, has been associated with high gastric residuals and an increased risk of aspiration [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous nutrition has been linked to an increased incidence of hyperglycemia (which is independently associated with increased mortality), increased risk of infection, and increased morbidity in septic patients [ 9 , 10 , 11 ]. Enteral nutrition also carries risk and has been associated with an increased incidence of diarrhea, nausea, vomiting, bowel ischemia, pulmonary aspiration, and hyperglycemia [ 12 , 13 ]. Full enteral nutrition, in particular, has been associated with high gastric residuals and an increased risk of aspiration [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, the patient enters a recovery phase with enhanced anabolism, requiring more substrate. In contrast, the persistent inflammation, immunosuppression, and catabolism syndrome (PICS) may arise in some [9,18,28]. Metabolically, PICS is characterized by a persistent catabolic state and hormonal disruption leading to anabolic resistance and inflammation-induced cachexia [53].…”
Section: Current Understandingmentioning
confidence: 99%
“…However, clinical studies have failed to prove an unequivocal benefit of early high-dose nutrition support, and several prospective randomized clinical trials showed significant harm, including increased hyperglycemia, hepatic steatosis, and mortality [1][2][3][4][5]. In contrast, undernourishment is also common in ICU and post-ICU patients due to both prescription inadequacy and failure to reach the nutrition target [6][7][8][9][10][11][12]. A negative energy balance in critically ill patients is associated with increased morbidity, including increased length of hospital stay, infections, organ failure, prolonged mechanical ventilation, and even mortality [2,13].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence in the literature that most of these conditions are characterized by hypermetabolism, due to the action of proinflammatory cytokines. 42,43 Unlike many clinical and epidemiological studies, that define malnutrition as a risk factor for infection and poor outcome, [44][45][46] studies that define clinical complications as a risk factor for malnutrition are rare. Pinchcofsky and…”
Section: Risk Factors For Malnutritionon During Hospitalizationmentioning
confidence: 99%